THE IMPLEMENTATION OF PICTURE SERIES AS MEDIA IN TEACHING WRITING OF A NARRATIVE TEXT OF THE TENTH GRADERS OF SENIOR HIGH SCHOOL (RETAIN, 2013)
Students are regarded still have difficulty in writing activity. So, a teacher should be creative in teaching of writing. Media is suggested to be used and pictures are visual aids that are simple, easy to produce, and relatively cheap. The appropriate composition for writing excercise is narrative text. So, there are two research question in this study, first is “How are the picture series used to teach students of senior high school in writing narrative text?” and “How is the students’ writing of narrative text after the implementation of picture series in teaching writing of a narrative text?”. Admittedly, writing to understand for oneself easily spills over into writing to share one’s understanding with others. Dealing with writing activity the use of picture series may be motivating and interesting. Pictures have an excellent device for providing both a purpose and content for writing. A picture series provide non-verbal cues for manipulation practice. It also provides students with information to refer to, including objects, actions, events, and a relationship. When pictures are used, a meaningful context is created. While, There are two components which become the important thing in writing narrative text. Those are language features and generic structure. The writer uses descriptive qualitative design in order to obtain the information. The data of the study is the teacher’s activity and the students’ composition that are collected in form of field-notes. Then, the data are analyzed qualitatively in descriptive way. The data are obtained through three times observation during three meetings that focus in learning how to write a narrative text using picture series as media from the generic structure and language features. It is found that teacher has a different technique in using picture series as media in writing narrative text to the tenth graders of senior high school which helps the students in composing a narrative text from its generic structure and language features that can be seen from students’ composition. A Picture series is regarded as one of alternative media which help both of the teacher and the students in teaching and learning of writing of narrative text. It is hoped that further research would be done with different techniques to enrich our understanding of using Picture Series as an alternative media in writing narrative. Keywords Writing, Picture Series, and Narrative Text